Optimization of Social Fund Collection Through Collaboration of Zakat Management Organizations and Islamic Banking in Indonesia Using Analytic Network Process (ANP) Method - Wardi, Novi; Hamid, Abdul; Suhendra; Hasan, Asyari; Rusydiana, Aam Slamet (UPT Publikasi Ilmiah UNISBA, 2025)
Zakat has an important role in improving welfare and social justice in the community, and has collaborated with Islamic banking to increase zakat collection. However, strategic collaboration between Zakat Collection Institutions (LAZ) and Islamic banks is still not optimal, especially in creating a more inclusive and integrated zakat ecosystem. This study aims to examine the form of strategies in efforts to optimize the collection of social funds (Zakat, Infaq, and Alms) in Indonesia through cooperation between the Zakat Management Organization and Sharia Banking. The method used in this study was the Analytic Network Process (ANP) method, with a total of 16 respondents selected through purposive sampling based on their relevance and competence to the research topic. The results of the study show that in the aspect of problems and solutions, the main priority is regulatory indicators, with an average value of 0.332 for problems and 0.329 for solutions. Then, in terms of the proposed optimization strategy, including strengthening regulations (0,262), aligning bank policies and strategies (0,255), increasing human resource competence (0,241) and developing innovative and varied products (0,241), which can significantly increase ZIS fundraising through collaboration between the Zakat Management Organization (ZMO) and Islamic Banking (IB). This study also provides a number of recommendations for regulators, practitioners, and academics to further improve the quality of their competencies and resources, as well as to review the implementation of regulations and their impact.